Development of spirulina for the manufacture and oral delivery of protein therapeutics - Jester, Benjamin W.; Zhao, Hui; Gewe, Mesfin; Adame, Thomas; Perruzza, Lisa; Bolick, David T.; Agosti, Jan; Khuong, Nhi; Kuestner, Rolf; Gamble, Caitlin; Cruickshank, Kendra; Ferrara, Jeremy; et al. (Nature biotechnology, 2022)
The use of the edible photosynthetic cyanobacterium Arthrospira platensis (spirulina) as a biomanufacturing platform has been limited by a lack of genetic tools. Here we report genetic engineering methods for stable, high-level expression of bioactive proteins in spirulina, including large-scale, indoor cultivation and downstream processing methods. Following targeted integration of exogenous genes into the spirulina chromosome (chr), encoded protein biopharmaceuticals can represent as much as 15% of total biomass, require no purification before oral delivery and are stable without refrigeration and protected during gastric transit when encapsulated within dry spirulina. Oral delivery of a spirulina-expressed antibody targeting campylobacter—a major cause of infant mortality in the developing world—prevents disease in mice, and a phase 1 clinical trial demonstrated safety for human administration. Spirulina provides an advantageous system for the manufacture of orally delivered therapeutic proteins by combining the safety of a food-based production host with the accessible genetic manipulation and high productivity of microbial platforms. Spirulina is used to manufacture a therapeutic antibody against campylobacter.